Unmet need for modern contraception by HIV status: findings from community-based studies implemented before and after earlier ART initiation program in rural Tanzania - Denna Mkwashapi; Jenny Renju; Michael Mahande; Alison Wringe; John Changalucha; Mark Urassa; Jim Todd (BMC, 2023)
Abstract Background Tanzania Health policy insists on the need to provide all women access to contraception despite HIV status. We used data from two HIV epidemiologic serological surveys carried out at different periods of ART provision in rural Tanzania to assess the level of unmet need for modern contraception by HIV status and associated factors. Methods We performed secondary data analysis of two surveys conducted at the Magu Health and Demographic Surveillance System site, in Mwanza, Tanzania. Information on unmet need for modern contraception was derived from fertility desire and contraception use. Unmet need, HIV status, and socioeconomic and demographic variables were analysed. The percentage of women with unmet needs for modern contraception by HIV status is presented for the 2012 and 2017 surveys. Bivariate and multivariate analyses using logistic regression were used to investigate associated factors showing adjusted odds ratios (aORs) and 95% confidence intervals (95% CIs). Results Data from 3352 and 3196 women aged 15-49 years collected in the 2012 and 2017 surveys, respectively, were analysed. The percentages of women with unmet needs for modern contraception in the 2012 and 2017 surveys were 30.9% (95% CI 29.4-32.6) and 31.6% (95% CI 30.0-33.3), respectively. The unmet need for modern contraception was 26% lower in HIV-uninfected women in 2012 (aOR = 0.74; 95% CI 0.569-0.973); p = 0.031). Risk factors for unmet need for modern contraception in 2012 were HIV uninfected (adjusted OR = 0.74; 95% CI 0.569-0.973); p = 0.031), married marital status (adjusted OR = 0.768; 95% CI 0.743-0.794); p < 0.0001), higher education (adjusted OR = 0.768; 95% CI 0.743-0.794); p < 0.0001), and taking alcohol (adjusted OR = 0.768; 95% CI 0.743-0.794); p < 0.0001). Only two factors were associated with unmet need for modern contraception in 2017: married marital status (adjusted OR = 0.46; 95% CI 0.305-0.722); p = 0.001) and women who earned for their families (aOR = 0.66; 95% CI 0.494-0.887); p = 0.006). Discussion Nearly one-third of women had an unmet need for modern contraception, which was lower in HIV-uninfected women than in WLHIV-infected women. The study has identified women whose demand for contraception has not been met: WLHIV, post marital women, women with low education and women who were reported to earn money for their families. Family planning interventions should be tailored to these groups of women.